Sleep and serotonin modulate paracapsular nitric oxide synthase expressing neurons of the amygdala - Bocchio, M; Fisher, S; Unal, G; Ellender, T; Vyazovskiy, V; Capogna, M (Society for Neuroscience, 2016)
Unraveling the roles of distinct neuron types is a fundamental challenge to understanding brain function in health and disease. In the amygdala, a brain structure regulating emotional behavior, the diversity of GABAergic neurons has been only partially explored. We report a novel population of GABAergic amygdala neurons expressing high levels of neuronal nitric oxide synthase (nNOS). These cells are predominantly localized along basolateral amygdala (BLA) boundaries. Performing ex vivo patch-clamp recordings from nNOS+ neurons in Nos1-CreER;Ai9 mice, we observed that nNOS+ neurons located along the external capsule display distinctive electrophysiological properties, axonal and dendritic arborization, and connectivity. Examining their c-Fos expression, we found that paracapsular nNOS+ neurons are activated during a period of undisturbed sleep following sleep deprivation, but not during sleep deprivation. Consistently, we found that dorsal raphe serotonin [5-hydroxytryptamine (5-HT)] neurons, which are involved in sleep–wake regulation, innervate nNOS+ neurons. Bath application of 5-HT hyperpolarizes nNOS+ neurons via 5-HT1A receptors. This hyperpolarization produces a reduction in firing rate and, occasionally, a switch from tonic to burst firing mode, thereby contrasting with the classic depolarizing effect of 5-HT on BLA GABAergic cells reported so far. Thus, nNOS+ cells are a distinct cell type of the amygdala that controls the activity of downstream neurons in both amygdaloid and extra-amygdaloid regions in a vigilance state-dependent fashion. Given the strong links among mood, sleep deprivation, and 5-HT, the recruitment of paracapsular nNOS+ neurons following high sleep pressure may represent an important mechanism in emotional regulation.